2016
DOI: 10.1007/s00280-016-3005-y
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase II study of vorinostat in combination with intravenous fludarabine, mitoxantrone, and dexamethasone in patients with relapsed or refractory mantle cell lymphoma: an interim analysis

Abstract: V-FND is effective in patients with relapsed or refractory MCL. However, significant toxicities were hurdles to sustained V-FND therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In 2012, a phase II study for vorinostat combined with fludarabine, mitoxantrone, and dexamethasone (V-FND) in patients with relapsed or refractory MCL was conducted and resulted in 77.8% ORR and 9.3 months median PFS (CISL 1201). We concluded that V-FND is an effective regimen for relapsed or refractory MCL; however, significant hematologic adverse events including neutropenia (grade 3/4 in 50%) and thrombocytopenia (grade 3/4 in 35%) were not negligible [52].…”
Section: Other Subtypes Of B-cell Neoplasmsmentioning
confidence: 79%
“…In 2012, a phase II study for vorinostat combined with fludarabine, mitoxantrone, and dexamethasone (V-FND) in patients with relapsed or refractory MCL was conducted and resulted in 77.8% ORR and 9.3 months median PFS (CISL 1201). We concluded that V-FND is an effective regimen for relapsed or refractory MCL; however, significant hematologic adverse events including neutropenia (grade 3/4 in 50%) and thrombocytopenia (grade 3/4 in 35%) were not negligible [52].…”
Section: Other Subtypes Of B-cell Neoplasmsmentioning
confidence: 79%
“…Histone-deacetylase (HDAC) inhibitors belong to innovative anticancer drugs. Unfortunately, HDAC inhibitors tested so far (vorinostat, panobinostat, and abexinostat), single-agent or in combination with various anti-lymphoma drugs, demonstrated modest anti-MCL efficacy in clinical trials published so far [60,61,62,63,64]. Mutations in SMARCA4 have been associated with poor response to ibrutinib plus venetoclax therapy through upregulation of BCL2L1/BCL-XL [65].…”
Section: Recurrent Molecular/cytogenetic Lesionsmentioning
confidence: 99%
“…Only five HRQoL studies were identified for inclusion in the review: three phase II single-arm trials [28][29][30], one publication of patient-reported outcomes in a phase III randomized controlled trial (RCT) (MCL-3001) [31], and one retrospective observational study [24]. Two studies were conducted in the US [28,29], one each in the Republic of Korea [30] and Switzerland [24], and one was multinational [31]. All five used cancer-specific (EORTC QLQ-C30 or FACT-G) or lymphoma-specific (FACT-Lym) instruments.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%